Effect Of The Bagging Configuration On The Properties Of Vacuum-Bagging-Only (Vbo) - Oven Cured In Complex-Shaped Composites - Hassan, Muhmimad Hafiz (2014)
With the growing needs of the aerospace industry to produce larger composite components at reduced costs, Out-of-Autoclave (OOA) manufacturing technology is perhaps the answer for the problem. However, the development work of the OOA process using prepreg materials to achieve minimum void content without high external pressure from the autoclave proved to be a major challenge. The research study focused specifically on the vacuum bagging process. In the initial study, eight bagging configurations which consist of three main processing parameters, including the use of release film (PTFE) , edge breather and the intensifier were proposed to improve the quality of the L-shaped laminate composites. The specimens were assessed based on degree of uniformity (DOU) and void contents levels. The results were subsequently evaluated using the analysis of variance (ANOYA) to determine the percentage of influence of the processing parameters to the quality improvement. The experimental results indicated that the use of PTFE has contributed 37.45% to the significant void formation at the corner section. In contrast, the edge breather (YBO) and intensifier successfully reduced the void content level by 19.64% and 29.41 %, respectively.